Wave Overtopping of a Porous Structure: Numerical and Physical Modeling - Reis, M. T. (2009)
This paper illustrates the application of the new version of a nonlinear shallow water numerical model, AMAZON, to study the mean wave overtopping discharge at a porous breakwater that protects the Portuguese harbor of Póvoa de Varzim. The results are compared with two-dimensional physical model data collected at the National Civil Engineering Laboratory, Portugal. The implications of using different porous flow parameters in the Forchheimer equation for stationary turbulent flow within the porous layer of the breakwater are discussed. The maximum velocity that the water can reach during the exchange between the free-flow and porous layers has been included as an input to AMAZON and its impact on the overtopping results is analyzed. A suitable choice of the values of the porous flow parameters and of the maximum velocity leads to a good agreement between the AMAZON results and the data. The specified maximum velocity was found to be the parameter which mostly affects the obtained results.